GWAS identifies risk locus for erectile dysfunction and implicates hypothalamic neurobiology and diabetes in etiology - Bovijn, J; Jackson, L; Censin, J; Chen, CY; Laisk, T; Laber, S; Ferreira, T; Pulit, SL; Glastonbury, CA; Smoller, JW; Harrison, JW; Ruth, KS; et al. (Cell Press, 2018)
Erectile dysfunction (ED) is a common condition affecting more than 20% of men over 60 years, yet little is known about its genetic architecture. We performed a genome-wide association study of ED in 6,175 case subjects among 223,805 European men and identified one locus at 6q16.3 (lead variant rs57989773, OR 1.20 per C-allele; p = 5.71 × 10−14), located between MCHR2 and SIM1. In silico analysis suggests SIM1 to confer ED risk through hypothalamic dysregulation. Mendelian randomization provides evidence that genetic risk of type 2 diabetes mellitus is a cause of ED (OR 1.11 per 1-log unit higher risk of type 2 diabetes). These findings provide insights into the biological underpinnings and the causes of ED and may help prioritize the development of future therapies for this common disorder.